Resolving an inherent controversy: How pesantren’s philosophical ideals confront the reality of bullying - Uswatun Hasanah; Khoirul Umam Addzaky (Al'Adalah, 2025)
This article examines how pesantren leaders and educators operationalise philosophical values embedded in the pesantren tradition to design a contextual anti-bullying program. Using a qualitative case study of Pesantren Nurul Yaqin (Indonesia), the study triangulates in-depth interviews with eight key participants (a pesantren leader, five educators, and two students), participatory observation, and document analysis. The research team analysed the data through iterative thematic coding. The findings suggest that bullying in pesantren is repeated peer aggression sustained by power imbalance. At the same time, a strong moral ecology regulates institutional life and helps contain severe incidents. At Pesantren Nurul Yaqin, four ideals, such as tawadhu’, ukhuwah Islamiyah, silaturahim, and ihsan, function as moral anchors that restrain domination, strengthen belonging, and activate prosocial defending. However, the study also identifies the limits of informal norms; leaders and peers may apply values unevenly, and those norms often fail when victims hesitate to disclose harm. This article proposes a values-based, Whole-School Approach-aligned protocol that formalises local wisdom into safeguards, including a confidential reporting mechanism, a peer-inclusive anti-bullying team, staged restorative responses, educator role-modelling, and parent or community engagement.